High-resolution sampling in the eastern tropical North Atlantic reveals episodic Saharan dust deposition: implications for the marine carbon sink - Matzenbacher, Blanda A.; Brummer, Geert-Jan A.; Prins, Maarten A.; Stuut, Jan-Berend W. (Frontiers in Marine Science, 2024)
In this study we present data collected between August 2017 and December 2018 from submarine sediment trap M1 located in the eastern tropical North Atlantic and determine lithogenic and biogenic fluxes, and grain-size distributions of aerosol dust. An unprecedented high sampling resolution of four days in combination with satellite imagery allowed the identification of thirteen major dust events of two types within the 468-day series. Seven dust events were classified as high-flux events identified by a deposition of >=25 mg m-2 d-1. The average dust deposition rate increased by 461.3% during these types of events. The remaining six events were characterized by a high composition of giant particles (>7.3 vol%). Seasonal variations of dust flux were recorded, with highest fluxes observed in spring at an average deposition rate of 14.8 mg m-2 d-1, and lowest fluxes in fall with an average rate of 8.6 mg m-2 d-1. The estimated total dust flux in the tropical North Atlantic was 4040.02 mg m-2 y-1. We suggest that most of the summer dust was likely transported over the sampling site at high altitudes while winter transport occurred closer to the sea surface, resulting in generally higher background fluxes. Grain-size distributions exhibited seasonal variations with increased occurrences of giant particles (>62.5 μm) in fall 2017 and spring, and less occurrences in winter and fall 2018. Grain-size sorting was high in spring and most variable in summer. Precipitation did not affect depositional fluxes or grain-size distributions of the aeolian dust significantly. Organic matter was deposited continuously at the sampling site with a deposition rate ranging from 14.4–862.25 mg m-2 d-1. Organic matter fluxes increased by 199.5% during high-flux dust events but decreased by 13.6% during anomalous grain-size events. Spring experienced the highest number of dust events (n=5). This unprecedented high-resolution dataset of dust deposition in marine sediment-traps enabled the distinction of dust events and their relation to organic matter flux. This suggests the possibility of a dust fertilization or mineral ballasting effect.